Enhancing cross-peak intensity in 2D-SLF spectroscopy - the role of equilibrium carbon magnetization in cross-polarization experiment - Das, Bibhuti B.; Ajithkumar, Thalasseril G.; Ramanathan, K. V. (Chemical Physics Letters, 2006)
A modification to the standard Hartmann-Hahn cross-polarization experiment has been proposed in which the initial 90 degrees pulses are applied both on the I and S spins. The inclusion of the available equilibrium polarization in the static magnetic field for the S spins is shown to have a beneficial effect for the 2D-SLF experiment, contributing to an increase in the cross-peak intensity and hence to a better resolution of the dipolar cross-peaks. (c) 2006 Elsevier B.V. All rights reserved.